Exploring Students’ Perceptions of Their Interest/Lack of Interest in Academic Work at a Five Year Government Secondary School in South Trinidad - Thomas, Vickey I. (My University, 2014)
This study explored students’ perceptions of their interest/lack of interest in their academic work. Data were collected through interviews with a focus group of six purposively selected fifth-form students at a secondary school in Trinidad and Tobago. Results of the study showed that the students identified internal and external influences as impacting their interest levels. They felt that teachers’ personalities and professional characteristics had a significant input, and expressed hurt and disappointment about the uncaring attitude of some teachers. They also pointed to parents and peers as influences on their school work. However, it was also revealed that some of the students’ own characteristics could have contributed to their interest levels. These included their performance goals orientation to school work and some psychosocial issues resulting from a need to establish their sense of independence. The students also felt that more academic support from significant others and more practical class activities could have increased their interest in the academic subjects taught at the school
Keywords: Perceptions; Secondary school students; Student attitudes; Case studies; Student motivation; Trinidad and Tobago